Closed Endotracheal Suctioning Impact on Ventilator-Related Parameters in Obstructive and Restrictive Respiratory Systems: A Bench Study - Fang Jung; Shang-Shing P. Chou; Shih-Hsing Yang; Jau-Chen Lin; Guey-Mei Jow (Applied Sciences, 2021)
A closed suctioning system (CSS) in patients with coronavirus disease 2019 (COVID-19) prevents spraying respiratory secretions into the environment during suction. However, it is not clear whether ventilation is maintained during the suction procedure, especially in patients with compromised pulmonary mechanics. This paper determines the effects of endotracheal tube (ETT) size, suction catheter size, and two lung mechanics (resistance and compliance) on ventilator-related parameters measured during suction. Suction was performed on an adult training lung, ventilated with either volume-controlled (VC-CMV) or pressure-controlled mandatory ventilation (PC-CMV), using ETT sizes of 6.5–8.0 mm paired with suction catheter sizes of 8–14 French (Fr). Peak inspiratory pressure (PIP) increased by 50% when the ETT’s ventilation area was less than 25 mm2 in size, especially in patients with high airway resistance ventilated with VC-CMV. Positive end-expiratory pressure (PEEP) levels significantly decreased when using 14 Fr SC during VC-CMV and fewer effects during PC-CMV. Change of expiratory minute volume increased with higher outer diameter of suction catheters and decreased with severe lung compliance during PC-CMV. The change in ventilator-related parameters were intently monitored in the patient whose pulmonary mechanic was compromised through the CSS endotracheal tube suctioning procedures in clinical airway management.